Spectral interferometry with waveform-dependent relativistic high-order harmonics from plasma surfaces - Dmitrii Kormin (Nature Portfolio, 2018)
High-order harmonic generation is explored in gases, solids and plasmas with moderate to high intensity lasers. Here the authors show spectral interferometry of HHG from relativistic plasma and its potential as a source of intense isolated attosecond pulses.